Pengaruh Gaya Belajar Terhadap Kinerja Akademis: Studi Empiris Tentang Mahasiswa/i Agribisnis Universitas Sultan Ageng Tirtayasa - Albert Donatus Simarmata; Siti Nurmaelani; Aenur Rohimah; Ila Susilawati; Nida Alya Zain (Lembaga Pengembangan Kinerja Dosen, 2023)
Cumulative Grade Point Average (GPA) is used as the final assessmen of graduates learning outcomes at the end of the study program. Factors that can influence the differences in learning achievement between each student can be categorized as internal factors and external factors. In this research, emphasis will be given to internal factors related to learning styles. Learning style is a characteristic possessed by individual in acquiring, organizing, and processing received information. The aim of this study is to examine the association between student learning styles and the Cumulative Grade Point Average (GPA). The sampling technique in this study is total sampling, and the method used in this study was the chi-square test of independence as the statistical method, and field study for data collection and analysis. The data used in this study was obtained from students of the Agribusiness Department at the Faculty of Agriculture, Sultan Ageng Tirtayasa University. The data collection technique used in this research is a questionnaire in which respondents are given the choice of GPA level above 3.5 or below 3.5, and also learning styles with the levels of learn by seeing, learn by hearing, learn by reading/writing, or learn by doing, which are disseminated through social media and analyzed to draw conclusions. In this study, a total of 67 respondents were collected. Based on the processed and analyzed data, the result of H0 is not rejected, and it can be concluded that there is no association between learning styles and GPA produced.